Kulturforskningens möjligheter i det nya forskningspolitiska landskapet - Brändström, Dan (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2008)
This article positions Swedish cultural research in a wider, European context. It shows how cultural components are growing in importance in the European Union, and that this trend for cultural policy also makes greater space for cultural research. Brändström argues that the Swedish debate tends to lag behind the European trends, but sees positive signs in the increasing collaboration between universities. He predicts that the competition between universities for skilled researchers will further increase, that there will be even more cooperation, and that older, established units will have an advantage in this process. A conclusion is that open and flexible organisations like the ACSIS, with its transdisciplinary networking, are well suited for the new situation.